The effects of combining PETTLEP imagery and action observation on bicep strength: A single-case design - Smith, D.; Romano-Smith, S.; Wright, D. J.; Deller-Rust, W.; Wakefield, C. J. (Journal of Applied Sport Psychology, 2020)
We investigated the effects of PETTLEP imagery combined with action observation on bicep curl performance. Using a single-case design, four participants completed a baseline phase followed by PETTLEP imagery with and without an observational aid. Results indicated that using an observational aid in conjunction with PETTLEP imagery can improve bicep curl performance, but not to a greater degree than PETTLEP imagery alone. This indicates that observational aids may not be an essential addition to imagery interventions. The study highlights further the benefit of using PETTLEP imagery for enhancing strength performance, which should be considered by practitioners delivering resistance training programs.